Pemikiran Ismail Al-Faruqi tentang Islamisasi Ilmu dan Kaitannya dengan Pendidikan Agama - Aggil Husni Almunawar; Salis Nurhidayah; Nafilatul Mubarokah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Medicine is one of the human endeavors to maintain health and sustain life. In practice, several types of treatment use substances or objects prohibited in Islam, such as alcohol, pork, and other impure substances. This issue has given rise to differing views among Islamic scholars regarding the legality of their use, particularly in emergencies. This study aims to determine the legality of medical treatment using prohibited substances from an Islamic perspective, based on the Quran, Hadith, and the opinions of Islamic scholars. The research method used was library research with a descriptive-analytical approach through a review of various Islamic literature. The results indicate that the basic law for using prohibited substances for treatment is haram. However, in emergencies where halal alternatives with equivalent benefits are not available, their use can be permitted under certain conditions, such as urgent need, expert recommendation, and avoidance of excessive use. Thus, Islam upholds the principle of halal while providing convenience for the community in certain circumstances. Keywords: Medicine, Haram Substances, Islamic Law, Emergency, Halal Medicine